Temperature predicts the rate of molecular evolution in Australian Eugongylinae skinks. (1st February 2022) - Ivan, Jeremias; Moritz, Craig; Potter, Sally; Bragg, Jason; Turakulov, Rust; Hua, Xia
Abstract: Temperature differences over time and space have been hypothesized to cause variation in the rate of molecular evolution of species, but empirical evidence is mixed. To further test this hypothesis, we utilized a large exon‐capture sequence data of Australian Eugongylinae skinks, exemplifying a radiation of temperature‐sensitive ectotherms spanning a large latitudinal gradient. The association between temperature (and other species traits) and long‐term substitution rate was assessed based on 1268 sequenced exons of 44 species pairs from the Eugongylinae subfamily using regression analyses. Temperature is the strongest, positively correlated predictor of variation in substitution rate across the Australian Eugongylinae. It explains 45% of variation in synonymous substitution rate, and 11% after controlling for all the other factors. Synonymous substitution rate is also negatively associated with body size, with a 6% variation explained by body size after controlling for the effects of temperature. Other factors are not associated with synonymous substitution rate after controlling for temperature. Overall, this study points to temperature as a strong predictor of the molecular evolution rate in the Eugongylinae subfamily, and demonstrates the power of large‐scale exonic data to identify correlates of the rate of molecular evolution.